Duck‐origin H5N6 avian influenza viruses induce different pathogenic and inflammatory effects in mice. Issue 6 (31st December 2020) - Xiang, Bin; Song, Jie; Chen, Libin; Liang, Jianpeng; Li, Xin; Yu, Deshui; Lin, Qiuyan; Liao, Ming; Ren, Tao; Xu, Chenggang
Abstract: Since 2013, H5N6 highly pathogenic avian influenza viruses have caused considerable economic losses in the poultry industry and have caused 24 laboratory‐confirmed human cases. In this study, we isolated nine (B1–B9) H5N6 viruses from healthy ducks in Guangdong Province, Southern China from December 2018 to April 2019. Phylogenetic analysis revealed that B1, B2, B3, B4, B5, B7, B8, and B9 clustered into the G1.1 genotype and shared high sequence similarity with human H5N6 isolates from Southern China in 2017 and 2018. Meanwhile, B6 clustered into the G1.1.9 genotype. The hemagglutinin (HA), neuraminidase (NA) and nonstructural protein (NS) gene segments of B6 were closely related to the human H5N6 isolates, while the other genomic segments were closely related to H5N6 viruses isolated from waterfowl in Southern China. Compared to B7, B6 had higher pathogenicity and induced stronger inflammatory responses in mice. B6 carried a full‐length PB1‐F2 protein (90 aa), while the rest carried an 11‐amino acid C‐terminal‐truncated PB1‐F2. The PB1‐F2 protein may increase the virulence of B6 compared to that of B7. Our findings provide insight into the pathogenic mechanisms of H5N6 viruses in mammals and emphasize the need for continued surveillance of circulating H5N6 viruses in ducks.